Can rainmakers justify their pay? The role of investment banks in REIT M&As - Zhang, Weiwei; Sun, Tiezhu; Goh, Patrick Han Lin; Wang, Zilong; Mansley, Nick (International Journal of Strategic Property Management, 2021)
This study explicitly rejects the prima facie proposition that the top-tier investment banks are capable of delivering supernormal value creation to the shareholders of a REIT acquirer in a corporate acquisition. Using the event study method, we find that REIT acquirers advised by market-leading investment banks suffer an average cumulative abnormal return of −4.41% following the M&A announcement, whereas REIT acquirers advised by non-top-tier investment banks only suffer an average cumulative abnormal return of −1.49%. The evidence shows that the contemporary practice of employing investment banks based on the prestige of the advisory firms could potentially result in value-destroying M&As for the REIT acquirers.